2018
DOI: 10.3122/jabfm.2018.03.170263
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Health Insurance Support Tools in Community Health Centers

Abstract: Background: Health information technology (HIT) provides new opportunities for primary care clinics to support patients with health insurance enrollment and maintenance. We present strategies, early findings, and clinic reflections on the development and implementation of HIT tools designed to streamline and improve health insurance tracking at community health centers. Methods: We are conducting a hybrid implementation-effectiveness trial to assess novel health insurance enrollment and support tools in prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Qualitative data collection included ethnographic observation and semi-structured interviews with key stakeholders at CHCs focused on barriers and facilitators to adoption of the enrollment tool were also conducted. Details about the implementation of the tool and differences in tool adoption between the two intervention arms appear elsewhere [ 40 42 ]. To summarize the findings of the implementation trial: we found that both arms used the tool though adoption was low (16%), but uptake was higher in Arm 2 (received practice coaching).…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative data collection included ethnographic observation and semi-structured interviews with key stakeholders at CHCs focused on barriers and facilitators to adoption of the enrollment tool were also conducted. Details about the implementation of the tool and differences in tool adoption between the two intervention arms appear elsewhere [ 40 42 ]. To summarize the findings of the implementation trial: we found that both arms used the tool though adoption was low (16%), but uptake was higher in Arm 2 (received practice coaching).…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative data collection continued through July, 2018. The intervention included the enrollment tool, educational materials, 'beta testing,' and facilitation which are described below [12].…”
Section: Study Design and Interventionmentioning
confidence: 99%
“…The intervention included the enrollment tool, educational materials, 'beta testing,' and facilitation which are described below. 12 The Enrollment Tool: As described in Table 1, the enrollment tool consisted of an electronic fillable 'form' which appeared alongside typical patient registration processes within the EHR. This form was intended for use by enrollment assisters or other staff who help patients or community members with registration or insurance enrollment.…”
Section: Study Design and Interventionmentioning
confidence: 99%